AWARENESS OF PLASTIC POLLUTION AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2025)
The increased production and widespread utilization of plastics, however, has its own negative impacts on the globe because a lot of disposed plastic products end up becoming litter, waste, and pollution. Human misuse of plastic is one of the major challenges faced today. The aim of the study was to assess the awareness about plastic pollution of the environment among dental students.t has been discovered that every one of the plastic classes has an alternate piece and in this manner conveys its own damages on human life A cross sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students aged between 19-25 years. The questionnaire involved information on the individual and socio demographic characteristics. Questions relating to the awareness of plastic pollutions, its causes and effects and preventive measures were provided for answering. The responses were recorded and analysed. 89% of the respondents were aware of the harmful effects plastic pollution. 72 % said plastic pollution is because of industrial waste, 28% said because of domestic waste. 84 % were aware of damage to marine environment. 92 % were aware of damage to soil environment. 65% are aware of reusable plastics. The awareness levels with regards to the plastic pollution is high among dental students. However more rigorous educational and awareness programs should be undertaken to educate the other students and general public.